EKSISTENSI RAKUT SITELU DALAM PENERAPAN SISTEM KEKERABATAN MASYARAKAT DI DESA SUKANALU KABUPATEN KARO - Nurul Rezeki Siregar,; Annisa Mahar Hani,; Lila Pelita Hati,; Lestari Dara Cinta Utami Ginting, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Rakut sitelu is a kinship system used by the Karo people. The Rakut Sitelu consists of Kalimbubu, Mondaya, and Anak Beru. This relationship has five basic clans as ties and a foundation consisting of Karo-karo, Ginting, Tarigan, Sembiring, and Perjuangann-angin. The background of this research is the Rakut sitelu culture in Sukanalu Village, where as time goes by, more and more foreign cultures (outside the Karo culture) are present and assimilate in the region. The research used four stages in the historical method, heuristics, verification, interpretation, and historiography. At the heuristic stage, interviews were conducted with traditional activists as well as the head of the village of Sukanalu, and some literature as a reference source. The results of the study show that in the village of Sukanalu Rakut Sitelu is still implemented and forms a single kinship, namely for immigrant communities who are not ethnic Karo because of the inclusion of various ethnicities in Sukanalu Village. It is the responsibility of traditional leaders, village leaders and also the community to continue to introduce every Karo culture and tradition to young people so that it does not disappear over time.